Online word-of-mouth and market structure - Santos, Carlos Daniel (2022)
Hotels adjust their product offerings depending on demand and competition faced. In this article I document the increase in average hotel quality as measured by online ratings, following the 50% increase in the number of tourists between 2008 and 2011. This change in quality is heterogeneous across hotel type. An increase in quality from high quality hotels positively influences other high quality hotels while increasing quality from low quality hotels positively influences other low quality hotels. Effects across quality levels (i.e. low on high and vice-versa) are insignificant. Finally, I quantify the gains from online ratings. Using a nested logit demand model I estimate that a one standard deviation increase in rating is associated with a 27% increase in demand. As a comparison, a 1 star increase in hotel class generates an approximate 70% increase in demand. Furthermore ratings are substantially more important for hotels with less stars, confirming the predictions that hotels with a lower signal, have more to gain from the existence of online user generated content.